Adoption of joint village land use planning (JVLUP) by the Government of Tanzania to increase tenure security for livestock keepers - CGIAR Research Program on Livestock (2019)
ILRI and partners including Government of Tanzania (GoT) piloted joint village land use planning (JVLUP) to protect shared resources including grazing lands for local livestock keepers in four clusters of villages covering 175,000 hectares of grazing land through the Sustainable Rangeland Management Project funded by IFAD (third phase 2016-2020). Now the GoT is upscaling JVLUP with a Global Environment Facility (GEF) grant of US$7.15 million across twenty-two villages in five districts, counting almost 13,000 households (69,555) people over 30,000 hectares.